Remoteness and maternal and child health service utilization in rural Liberia: A population–based survey - Avi Kenny (Journal of Global Health, 2015)
This study seeks to understand distance from health facilities as a barrier to maternal and child health service uptake within a rural Liberian population. Better understanding the relationship between distance from health facilities and rural health care utilization is important for post–Ebola health systems reconstruction and for general rural health system planning in sub–Saharan Africa.